Farmer's Perception of Rice Farming Insurance Program - Dwijayana, Indra; Prajanti, Sucihatiningsih Dian Wisika (Efficient: Indonesian Journal of Development Economics, 2021)
The purpose of this research is to examine the farmers perception of the insurance policy for rice farming in Kendal District, Kendal Regency and to find out the obstacles to these policies. This type of research is quantitative, using a non-probability method. Analysis of data using a Likert Scale based on the answer of 20 questions to measure the farmers perception of the rice farmers insurance program with total respondents as many as 96 people. In addition, the interview method is used to determine the barriers to farmers in participating in the rice farmers Insurance program. The results of the analysis show that farmers perception of the AUTP program in the Karangsari Village, Kendal Sub-District were classified as poor. This is because farmers face obstacles during the program. The suggestion of this research is that special and periodic program socialization should be held. In addition, the government should form a special team to assist farmers. This assistant is tasked with helping farmers from the start to claim losses. This officer is appointed from the local region ‘Gapoktan’. Penelitian ini bertujuan mengkaji persepsi petani terhadap kebijakan asuransi usaha tani padi di Kecamatan Kendal, Kabupaten Kendal serta mengetahui hambatan-hambatan kebijakan tersebut. Jenis penelitian adalah kuantitatif, menggunakan metode non-probabilitas. Analisis data menggunakan Skala Likert yang didasarkan pada jawaban dari 20 pertanyaan untuk mengukur persepsi petani terhadap program AUTP dengan total responden sebanyak 96 orang. Selain itu, metode wawancara digunakan untuk mengetahui hambatan-hambatan petani dalam mengikuti program AUTP. Hasil penelitian menunjukkan bahwa persepsi petani terhadap program AUTP di Kelurahan Karangsari, Kecamatan Kendal tergolong kurang baik. Hal ini disebabkan karena petani mengalami hambatan-hambatan selama mengikuti program. Berdasarkan hasil penelitian yang telah dilakukan, peneliti menyarankan agar diadakan sosialisasi program secara khusus dan berkala. Selain itu, pemerintah perlu membentuk tim khusus yang bertugas sebagai pendamping petani. Pendamping ini bertugas untuk membantu petani dari awal hingga klaim kerugian. Petugas ini ditunjuk dari gapoktan wilayah setempat.